2002
DOI: 10.1080/003655102760145816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral gas retention and oedema formation in decompressed rats by using a simple gravimetric method

Abstract: The brombenzene/kerosene gradient column was found to be a sensitive method for distinguishing between gas retention and oedema formation in decompressed animals. There was a higher gas retention in rats with a high bubble score compared to rats with a low bubble score. The major contribution to the change in specific gravity in decompressed animals is due to oedema formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The pathological effects of bubbles may cause a mechanical disruption of the tissue concerned, with the compression of noncompliant tissue of blood vessels and lymphatics, or from simply obstructing blood vessels (Nossum et al 1999). Several studies have shown reduced endothelial function after exposure to vascular bubbles (Nossum et al 1999;Hjelde et al 2002b;Brubakk et al 2005;Lambrechts et al 2013) and we have suggested that this may be a central mechanism in the development of serious decompression injury (Brubakk and Mollerlokken 2009). Albeit the link between VGE and DCS is far from clear, the assumption was made that a large bubble load would lead to the arterialization of VGE, which in turn would lead to neurological DCS, and subsequent neurological damage or BBB impairment.…”
Section: Discussionmentioning
confidence: 83%
“…The pathological effects of bubbles may cause a mechanical disruption of the tissue concerned, with the compression of noncompliant tissue of blood vessels and lymphatics, or from simply obstructing blood vessels (Nossum et al 1999). Several studies have shown reduced endothelial function after exposure to vascular bubbles (Nossum et al 1999;Hjelde et al 2002b;Brubakk et al 2005;Lambrechts et al 2013) and we have suggested that this may be a central mechanism in the development of serious decompression injury (Brubakk and Mollerlokken 2009). Albeit the link between VGE and DCS is far from clear, the assumption was made that a large bubble load would lead to the arterialization of VGE, which in turn would lead to neurological DCS, and subsequent neurological damage or BBB impairment.…”
Section: Discussionmentioning
confidence: 83%
“…Vascular bubbles can have mechanical, embolic and biochemical effects (Mollerlokken et al 2011). Entrapment of these bubbles may lead to cellular injury, cerebral edema and increased permeability of the blood–brain barrier (BBB) (Hjelde et al 2002; Kaakkola et al 1982). Acute effects can be caused by extravascular bubbles producing pain, or vascular bubbles obstructing and causing stroke-like symptoms (Vann et al 2011).…”
Section: Introductionmentioning
confidence: 99%